Good School Governance Through Technological Transformation: Implementation of Digital Attendance at SMK PGRI Mojoagung to Meet Global Demands - Ghafur, Zakky; Mutia Mahmudah; Winarsih Vilia Sari; Rulli Fatmawati; Rita Nurmalia; Fina Tri Handayani; Winda Nurlaily Rafikalia Iskandar (Edumedia Solution, 2026)
This community engagement activity aimed to implement a digital attendance system using spreadsheets and QR Codes at SMK PGRI Mojoagung, which previously used manual attendance. The main problems faced by the school were the low efficiency of attendance data recapitulation and limited administrative transparency, which affected the quality of school governance. The implementation method consisted of an initial survey, interviews with school partners, digital system design, QR Code preparation for student cards, user training, and implementation evaluation involving 180 tenth-grade students. The results showed improved efficiency in attendance recording, greater data accuracy, easier real-time monitoring, and stronger communication between the school and parents through WhatsApp notifications. The activity also supported the application of good school governance principles through more standardized procedures, faster data updates, and traceable attendance records that can be used as evidence for school accreditation. However, implementation still requires attention to infrastructure readiness, user digital literacy, data integrity, and student personal data protection.